Rehabilitation interventions for persons with hip fracture and cognitive impairment: A scoping review. - Lauren Cadel; Kerry Kuluski; Walter P Wodchis; Kednapa Thavorn; Sara J T Guilcher (PLoS ONE)
Background Hip fractures are common fall-related injuries, with rehabilitation and recovery often complicated by cognitive impairment. Understanding what interventions exist, and in what settings, for people with hip fracture and co-occurring cognitive impairment is important in order to provide more evidence on rehabilitation and related outcomes for this population. Objective To examine the extent, nature, and range of literature on rehabilitation interventions for adults with hip fracture and cognitive impairment. Methods Articles were required to: include an adult population with hip fracture and cognitive impairment, include a rehabilitation intervention, and be published between January 1, 2000 and November 19, 2021. Articles were excluded if they were opinion pieces, study protocols, conference abstracts, or if they did not describe the rehabilitation intervention. Relevant articles were searched on the following electronic databases: MEDLINE, EMBASE, CINAHL Plus, APA PsycINFO, Cochrane Library, Web of Science, and the Physiotherapy Evidence Database. All articles were double-screened by two reviewers and disagreements were resolved through consensus. Data were extracted and synthesized using descriptive approaches. Results Seventeen articles were included in this scoping review. We identified a variety of interventions targeting this population; about half were specific to physical rehabilitation, with the other half incorporating components that addressed multiple aspects of the care journey. Interventions had varying outcomes and no studies qualitatively explored patient or family experiences. All intervations were initiated in hospital, with less than half including cross-sectoral components. About half of the articles described modifying or tailoring the intervention to the participants' needs, but there was limited information on how to adapt rehabilitation interventions for individuals with cognitive impairment. Conclusions More work is need to better understand patient, family, and provider experiences with rehabilitation interventions, how to tailor interventions for those with cognitive impairment, and how to successfully implement sustainable interventions across sectors.